2011
DOI: 10.1007/s11814-010-0445-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal layout of additional facilities for minimization of domino effects based on worst-case scenarios

Abstract: Accidents involving domino effects are more serious than other type of accidents. Although there have been studies on such accidents, it is still difficult to examine the actual factors and causes since the domino effect is influenced nonlinearly by factors involving flame, overpressure, and flying objects. We considered the case of adding new facilities to an existing system in a given site. The layout of new facilities suggests positions that minimize the domino effects, based on nonlinear optimization takin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The developed computer-aided module (MiniFFECT) sequentially allocates hazardous installations in a limited land [89]. This optimization approach was further improved to obtain the optimal plant layout minimizing the total weighted consequences of different escalation scenarios [90]. Besides, the research was also extended to minimize the total construction costs, including pipeline connection cost, protection cost, and land-use cost [91].…”
Section: ) Layout Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed computer-aided module (MiniFFECT) sequentially allocates hazardous installations in a limited land [89]. This optimization approach was further improved to obtain the optimal plant layout minimizing the total weighted consequences of different escalation scenarios [90]. Besides, the research was also extended to minimize the total construction costs, including pipeline connection cost, protection cost, and land-use cost [91].…”
Section: ) Layout Optimizationmentioning
confidence: 99%
“…Based on protection principles, decision-making tools are needed to identify the best strategy according to decision criteria. Decision-making for inherent safety strategies has drawn much attention, including comparative analysis [86,87], layout optimization [88,90,91], and inventory optimization [98]. The decision-making on safety barriers includes optimization of the allocation of safety barriers [104,105], cost-effective analysis [107] of the influence of costs on decision-making for safety barriers.…”
Section: A Summarization Of Current Research (1) Risk Assessment Of D...mentioning
confidence: 99%
“…There was a study that found 37.5 kW/m 2 is suitable as a thermal radiation criterion causing damage to facilities in an experiment that applied thermal radiation to a sample of an offshore platform, and propane was applied for the source material of thermal radiation [15]. Another study selected 37.5 kW/m 2 as the criterion for causing chain explosion under the influence of thermal radiation of process equipment and Liquefied Petroleum Gas (LPG) was applied for the source material of thermal radiation [16]. There was also a study that the separation distance between the propylene process equipment and the other facilities of chemical plant should be 37.5 kW/m 2 of thermal radiation, and propylene was applied for the source material of thermal radiation [17].…”
Section: Source Descriptionmentioning
confidence: 99%
“…Baser and Behnam proposed an emergency response plan for cascading post-earthquake fires in fuel storage facilities [24], and Misuri et al developed a method for assessing the performance of the safety barrier in Natech scenarios [21]. To date, the mitigation measures for domino effects mainly include inherent safety [25][26][27], safety barriers [28][29][30], emergency response [31][32][33], etc. However, such studies remain narrow in focus, dealing only with Natech events or domino effects.…”
Section: Introductionmentioning
confidence: 99%